2017
DOI: 10.1016/j.tetlet.2017.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective β-mannosylation via anomeric O-alkylation: Formal synthesis of potent calcium signal modulator acremomannolipin A

Abstract: Stereoselective β-mannosylation has been investigated via cesium carbonate-mediated anomeric O-alkylation of D-mannose-derived lactol with various electrophiles. It was found that electrophiles bearing trifluoromethanesulfonate (triflate) as the leaving group are most reactive. In addition, a highly efficient formal synthesis of potent calcium signal modulator acremomannolipin A has been achieved using this β-mannosylation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Previously, anomeric O ‐alkylation of 3,4,6‐tri‐ O ‐benzyl‐ d ‐mannose 7 with allyl bromide in the presence of Cs 2 CO 3 was found to afford allyl 3,4,6‐tri‐ O ‐benzyl‐ β ‐ d ‐mannoside 43 in 94 % yield ( β only) . Based on that, we conducted reaction progress kinetic analysis involving two different initial concentrations of mannose 7 , in order to establish whether monomeric cesium alkoxide 42 β or its dimeric form is the key reactive intermediate for this anomeric O ‐alkylation (Figure ) .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previously, anomeric O ‐alkylation of 3,4,6‐tri‐ O ‐benzyl‐ d ‐mannose 7 with allyl bromide in the presence of Cs 2 CO 3 was found to afford allyl 3,4,6‐tri‐ O ‐benzyl‐ β ‐ d ‐mannoside 43 in 94 % yield ( β only) . Based on that, we conducted reaction progress kinetic analysis involving two different initial concentrations of mannose 7 , in order to establish whether monomeric cesium alkoxide 42 β or its dimeric form is the key reactive intermediate for this anomeric O ‐alkylation (Figure ) .…”
Section: Resultsmentioning
confidence: 97%
“…of allyl bromide was added to this supernatant containing cesium alkoxide 42 in CDCl 3 and the resulting mixture was stirred at 40 °C for 24 hours to afford desired allyl 3,4,6‐tri‐ O ‐benzyl‐ β ‐ d ‐mannoside (cf. 43 , Scheme ) in 23 % yield. This result indicated that cesium alkoxide 42 β is the reactive species in the anomeric O ‐alkylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation